The development history and latest progress of Japan’s earthquake early warning business regulations and technical systems - Lin Zhu; Weiping Lian; Yumei Li; Hongbo Chen (地震科学进展)
The regulations and technical systems for earthquake early warning in Japan have been continuously updated and developed in recent years. Starting from February 1, 2023, long-term earthquake motion prediction information was officially included in the Japan earthquake warning release. Since 2015, the underwater observation network has been integrated into the early warning system, effectively shortening the time for the first warning of earthquakes occurring along the coast of the Japan Trench. In 2018, the PLUM method was introduced to enable the system to make earthquake motion predictions even when traditional methods fail. At present, efforts are focused on solving the problem of frequent occurrence of excessive earthquake motion prediction. The Japan Meteorological Agency has introduced the integrated IPF method by the end of 2023 to reduce the rate of excessive earthquake motion prediction. The problems encountered in the current development of earthquake early warning technology and applications in Japan, as well as the envisioned future key development directions, provide useful references for the development of earthquake early warning in China.